Do "sinners" shift when the sin is taxed? a policy analysis of the 2012 Philippine Sin Tax on gambling expenditure across income deciles - Onsana, Angelica V.; Panti, Manica M.
The Philippines ratified the Sin Tax Reform Law, or Republic Act 10351, in 2012, which aimed to increase the allocation of generated taxes directed to Department of Health’ (DOH) initiatives while decreasing rates of tobacco and alcohol consumption. In the Philippines, the sin tax is levied on the prices of tobacco goods and alcoholic beverages sold in the market. In other countries, gambling, or any game of chance activities, are also included in the said tax; however, this is not practiced in the Philippines. With this distinction, we hypothesize that an increase in the sin tax declaration of the government would lead Filipinos to consume more of their income intended for vices to indulge instead in gambling. Results show that there is no fixed spending behavior that could embody the populace’s gambling decisions and that it is more dependent on the household’s disposable income. Although alcohol consumption decreased across all deciles, this did not imply that there had been a shift in gambling expenditure for all deciles as well. It is also observed that the majority of the lower-income deciles tend to decrease their consumption of gambling in contrast to higher-income earners.